Peningkatan keterampilan menulis aksara jawa nglegena melalui model numbered heads together berbasis media kubus aksara jawa kelas III sekolah dasar - Wahyu Drajad Sitaresmi; Muhammad Ismail Sriyanto; Joko Daryanto (Didaktika Dwija Indria, 2019)
Abstract. The objective of this research is to raise Javanese alphabet nglegena writing skills at students on the third grade through the use of Numbered Heads Together model based on Javanese Alphabet Cube media. Research about Classroom Action executed in two cycles. Every cycle composes of planning, action, observation, and reflection. The subjects are 20 students and teacher of the third grade. Techniques of data collection are observation, interview, test, and documentation. Validity data test techniques used are validity of content and triangulation. Data analysis technique consists of data collection, data reduction, data display, and conclusion drawing. Based on the outcome of this research, it is obtained that the class’ average grade on pre-action is 49,03 with classical complement which is 5%. The class’ average grade in the first cycle increases to 70,5 with classical complement is 55%. Furthermore, the class’ average grade in cycle II increases again to 83,78 with classical complement is 90%. The conclusion is the use of Numbered Heads Together model based on Javanese Alphabet Cube media can raise Javanese alphabet nglegena writing skill at students on the third grade of SD N 3 Macanan, Kebakkramat, Karanganyar at the academic year 2018/ 2019.Keywords: Javanese alphabet nglegena writing skills, Numbered Heads Together models, Javanese Alphabet Cube media.